Sick child's feeding practices and associated factors among mothers with sick children aged less than 2 years in Gamo zone, southern Ethiopia. Does the participation of fathers contribute to improving nutrition? A facility-based cross-sectional study - Feven Masresha Hailu; Simegn Wagaye Kefene; Muluken Bekele Sorrie; Misgun Shewangezaw Mekuria; Tamirat Gezahegn Guyo (Frontiers Media S.A., 2023)
BackgroundChildren's nutritional status can decline rapidly during or after a common childhood illness unless additional nutritional requirements associated with the illness are considered. Therefore, this study was aimed at assessing a sick child's feeding practices and associated factors among mothers who have sick children under 2 years of age in southern Ethiopia.MethodsA facility-based cross-sectional study design was employed from 1 April 2022 to 30 April 2022. Data were collected through the questionnaire, entered into an open data kit (ODK), and exported into Statistical Packages for Social Sciences (SPSS) version 25.0 for analysis. A systematic random sampling technique was used to select study participants. Bivariable and multivariable logistic regression analyses were used to identify factors associated with sick child feeding practices. An adjusted odds ratio (AOR) with 95% confidence intervals (CIs) was used to determine the strength of the association. Statistical significance was declared at a p-value of <0.05.ResultsThe overall magnitude of mothers' good sick child feeding practices was determined to be 45.0% (95% CI: 41.03, 48.97%). Being urban residents, being employed, having antenatal care (ANC) visits, having postnatal care (PNC) visits, counseling about child feeding, and fathers' involvement in sick child feeding increased the likelihood of sick child feeding practices by 4.4, 2.10, 2.31, 3.54, 2.11, and 2.54 times, respectively.ConclusionSick child feeding practices were associated with having antenatal or postnatal visits, counseling about child feeding, and fathers' involvement in sick child feeding practices. Therefore, strengthening infant and young child feeding practices by showing special concern for the father's involvement is important to improve mothers' sick child feeding practices.